2019
DOI: 10.17113/ftb.57.01.19.5692
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Phytosterols, Rheology, Antioxidant Activity and Emulsion Stability of Salad Dressing with Cocoa Butter During Storage

Abstract: Addition of phytosterols and antioxidants to food may provide additional health benefits to consumers. Their stability in a food matrix may decrease during storage. Therefore, the objectives of this study are to formulate a salad dressing with cocoa butter and determine its phytosterol stability, antioxidant activity and physicochemical properties during storage. The cocoa butter was extracted using a supercritical CO2 extraction (green technology) and added to the formulated salad dressing (containing differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
4
2
Order By: Relevance
“…However, our results were lower than the ES values (81.8–88.2%) reported by Mohamad et al. ( 2019 ) who utilized cocoa butter as a stabilizer for salad dressings. According to Lozano‐Gendreau and Vélez‐Ruiz ( 2019 ), food emulsions and suspensions with high oil content (>50% w/w) may show lower values of EC and ES.…”
Section: Resultscontrasting
confidence: 93%
See 1 more Smart Citation
“…However, our results were lower than the ES values (81.8–88.2%) reported by Mohamad et al. ( 2019 ) who utilized cocoa butter as a stabilizer for salad dressings. According to Lozano‐Gendreau and Vélez‐Ruiz ( 2019 ), food emulsions and suspensions with high oil content (>50% w/w) may show lower values of EC and ES.…”
Section: Resultscontrasting
confidence: 93%
“…Similar findings have been reported by Perrechil et al (2010) for ES of commercial Italian salad dressings during 6 days of storage (50-65%). However, our results were lower than the ES values (81.8-88.2%) reported by Mohamad et al (2019) who utilized cocoa butter as a stabilizer for salad dressings. According to Lozano-Gendreau and Vélez-Ruiz (2019), food emulsions and suspensions with high oil content (>50% w/w) may show lower values of EC and ES.…”
Section: Emulsifying Capacity and Emulsion Stability Of Isdscontrasting
confidence: 97%
“…During storage for 50 days, the pH values decreased in all samples: by 4.2% (control), by 4.5% (CMAE), and by 9.8% (CMAEP) (Table 4). Probably, this decrease can be influenced not only by the chemical composition of the aronia fruits, but also due to the oxidation of the lipids present in cocoa butter used in manufacturing confectionery masses [55,56].…”
Section: Ph Variation In the Confectionery Massesmentioning
confidence: 99%
“…A considerable body of research has found that the molecular structure of emulsifiers (Chen, Rao, et al., 2016 ; Chen, Qiu, et al., 2016 ), water contents (Kim et al., 2015 ), and emulsification equipment and methods (Lignel et al., 2017 ; Raviadaran et al., 2019 ) have a substantial influence on the physicochemical stability of W/O emulsions. Moreover, the stability of W/O emulsions during long‐term storage is not only affected by intrinsic properties but also by extrinsic factors such as temperature and light (Mohamad et al., 2019 ). In addition, the oxidative deterioration of W/O emulsions persists in the digestion process after the consumption by consumers.…”
Section: Introductionmentioning
confidence: 99%